Developing Writers Across the Primary and Secondary Years: Growing into Writing - Chen, Honglin; Myhill, Debra; Lewis, Helen (Routledge, 2020)
Writing development and pedagogy is a high priority area, particularly with standardised testing showing declines in writing across time and through the years of schooling. However, to date there are relatively few texts for teachers and teacher educators which detail how best to enable the children to become confident, autonomous, and agentic writers of the future. Developing Writers Across the Primary and Secondary Years provides cumulative insights into how writing develops and how it can be taught across years of compulsory schooling. This edited collection is a timely and original contribution, addressing a significant literacy need for teachers of writing across three key stages of writing development, covering early (4-7 years old), primary (7-12 years old), and secondary years (12-16 years old) in Anglophone countries. Each section addresses two broader themes - becoming a writer with a child-oriented focus and writing pedagogy with a teacher-oriented focus. Together, the book brings to bear rigorous research and deep professional understanding of the writing classroom. It offers a novel approach conceiving of writing development as a dynamic and multidimensional concept. Such an integrated interdisciplinary understanding enables pedagogical thinking and development to address more holistically the complex act of writing.